2019
DOI: 10.18203/2320-6012.ijrms20193913
|View full text |Cite
|
Sign up to set email alerts
|

Neovascularization: topical effects of streptococcus thermophilus and low level laser therapy in treatment of diabetic wound in rats

Abstract: Background: Diabetic wound is a major socioeconomic debilitating problem in this society. Various treatment options are available but still it requires better treatment option. In diabetes mellitus the oxygenation to the tissues is reduced. In this study effects of low level laser therapy were compared with topical application of Streptococcus thermophilus on diabetic wounds that induces formation of new blood vessel and free radical scavenging system, a comparative study to get better treatment option for dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, it was observed that when Streptococcus thermophilus treatment and low-level laser therapy were used in combination, accelerated DW healing occurred. In addition, the combination promoted angiogenesis and collagen deposition at the site of injury [47].…”
Section: Therapeutic Potential Of Probiotics In Treating Dwmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was observed that when Streptococcus thermophilus treatment and low-level laser therapy were used in combination, accelerated DW healing occurred. In addition, the combination promoted angiogenesis and collagen deposition at the site of injury [47].…”
Section: Therapeutic Potential Of Probiotics In Treating Dwmentioning
confidence: 99%
“…In another study, Kumari et al (2019) examined the effect of Streptococcus thermophilus and low-level laser therapy on DW healing in male Albino diabetic rats. The results revealed that the topical application of saline did not lead to effective wound contraction while Streptococcus thermophilus showed a reduction in oxidative stress and promoted DW healing.…”
Section: Therapeutic Potential Of Probiotics In Treating Dwmentioning
confidence: 99%
“…Aside from osteomyelitis research, the effect of LLLT on bone repair was thoroughly carried out and showed stimulation of bone production;[ 30 31 32 ] therefore, the positive effect of this treatment modality can be postulated. A stimulating effect was recorded in terms of blood and lymph neovascularisation,[ 33 34 ] synthesis of RNA, DNA, collagen and its precursors, as well as positive effects on the levels of prostaglandin, phagocyte cytoplasmic granules, cell proliferation and production of adenosine-5’- triphosphate. [ 35 36 ] Furthermore, an existent penetration of LED 635-nm low-level light through the soft and hard tissues of the jaws was demonstrated[ 37 ] which implies that the complete jaw bone thickness receives therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%